2017
DOI: 10.1093/dote/dox028
|View full text |Cite
|
Sign up to set email alerts
|

Peroral endoscopic myotomy versus surgical myotomy for primary achalasia: single-center, retrospective analysis of 74 patients

Abstract: Achalasia is a neurodegenerative motility disorder of the esophagus; dysphagia, weight loss, chest pain, and regurgitation are its main symptoms. Surgical myotomy (HM) is considered the gold standard treatment. However, peroral endoscopic myotomy (POEM) seems to be a safe and effective alternative option. The aim of this study is to compare the safety and efficacy of these techniques. From March 2012 to June 2015, 74 patients with symptomatic primary achalasia underwent myotomy. The two groups were compared in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
32
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 28 publications
1
32
0
3
Order By: Relevance
“…The studies comparing POEM with the current gold standard of myotomy, that is, LHM, have concluded that both the modalities are equally effective and safe . Besides equal efficacy, POEM was found to be associated with less blood loss, shorter operative time, less postoperative pain and analgesic use, shorter hospital stay, and quicker return to normal activities. Two studies compared the cost‐effectiveness of POEM with LHM and robotic LHM, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies comparing POEM with the current gold standard of myotomy, that is, LHM, have concluded that both the modalities are equally effective and safe . Besides equal efficacy, POEM was found to be associated with less blood loss, shorter operative time, less postoperative pain and analgesic use, shorter hospital stay, and quicker return to normal activities. Two studies compared the cost‐effectiveness of POEM with LHM and robotic LHM, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The literature on frequency of development of gastro‐esophageal reflux disease (GERD) diagnosed using objective modalities following POEM as compared with the other treatment modalities is scanty . In POEM, limited hiatal dissection is performed in contrast to LHM thereby theoretically reducing the chances of GERD.…”
Section: Methodsmentioning
confidence: 99%
“…On this issue different and contrasting data exist, mostly depending on how the reflux is measured: subjective recording of symptoms, 24-hour pH monitoring or the damage caused on the oesophageal mucosa as visualized by endoscopy. The study by de Pascale et al (15) reported a similar number of patients with symptoms and with positive pH monitoring in POEM and LHM patients, but a high number of patients with oesophagitis after POEM. Similar data have been observed by Werner et al (20) with 36% of patients with oesophagitis grade A and B after POEM and by Teitelbaum et al that reported 59.6% of patients with oesophagitis, but only 15% with symptoms, whilst pH monitoring results were abnormal in 31% of patients (23).…”
mentioning
confidence: 89%
“…One of these studies has been recently published on Diseases of the Esophagus by an Italian group (15). In this single center, retrospective study the Authors report on 74 myotomies for primary achalasia: 32 patients underwent POEM and 42 LHM.…”
mentioning
confidence: 99%
“…Si bien la técnica resulta atractiva, conlleva la necesidad de implementar equipos multidisciplinarios con amplia experiencia en endoscopia terapéutica y de ser efectuada en centros de referencia, además requiere una larga curva de aprendizaje y no está exenta de eventos adversos 5 . La POEM tampoco soluciona el reflujo gastroesofágico, que es causante de daño severo en un esófago sin posibilidad de depuración 6 . Quedan por aclararse aspectos tales como la eficacia en la acalasia con importante megaesófago y en los casos de ausencia de actividad contráctil simultánea del cuerpo esofágico, en los que el fracaso de las dilataciones y de la técnica Heller es importante.…”
unclassified